Guide méthodologique pour l'analyse spatiale du covid-19 dans les zones urbaines non métropolitaines du Brésil - João Pedro Pereira Caetano de Lima; Raul Borges Guimarães (Confins)
This article presents a methodological guide for analyzing COVID-19 at the intra-urban scale in non-metropolitan areas of south-central Brazil. To this end, it briefly discusses the COVID-19 pandemic and pertinent questions for making COVID-19 maps in different urban realities. It then presents different mapping techniques and how they can be implemented, especially in medium-sized cities. Point implementation, including proportional symbols and distribution in points; II. Zonal implementation with choropleth maps with some examples of epidemiological rates and bivariate choropleth maps; III. Surface implementation with maps using the Kernel Estimator; IV - spatial statistics maps and, finally, combination and synthesis maps, seeking to aggregate various pieces of information into a synthetic cartographic product. It is important to make it clear that the techniques and modes of deployment are subject to an assessment of the potential and weaknesses of the techniques given the type of data available. We therefore hope that this article will be useful for beginners in the fields of cartography and geography and for those who wish to improve their knowledge.